Manager–employee communication in the# MeToo Era: The role of gender similarity and context ambiguity in ethical leadership - Meeks, Lindsey; Howe, William (My University, 2020)
Sexual harassment is a widespread problem in the American workplace. Managers must understand how their employees perceive ethical leadership in this context. This includes current undergraduates—managers’ future employees. Undergraduates are entering the workforce in a climate of heightened awareness due to the #MeToo movement and federally required collegiate sexual violence training. Grounded in scholarship on ethical leadership and feminist standpoint theory, the experiment compares U.S. undergraduates’ perceptions of male and female managers across common workplace scenarios and examines their evaluations of managers’ traits and behaviors. Analysis reveals (a) what manager behavior is deemed ethical, (b) a general preference for female managers, and (c) that women evaluate female managers more positively than male managers. This study’s findings provide important implications for employee–manager communicative exchanges.
Keywords: Organizational Communication; Sexual Harassment; Ethical Leadership